(untitled) (Research, Society and Development, 2021)
The objective of this research was to evaluate the influence of the information contained in the packaging on the sensory profile of different brands of coconut yogurt. Three brands of yogurt were compared considering the laboratory evaluations in two conditions: blind and informed. In the latter case, the product was presented to the consumer in its original container (packaging containing the label). One hundred and two adult consumers of both sexes participated in the research. The results showed that product information significantly influences the sensory perception of some attributes by consumers. This occurred both in segmented groups and in individualized assessments. An ideal coconut yogurt was classified as creamy, homogeneous, with a fruit and aroma flavor, white color intensity, sweet flavor and smooth consistency. Already, attributes such as sour/acid flavor, no flavor, thick texture, firm consistency and liquid appearance were reported as more distant from an ideal product. Specific parameters such as sour/acid flavor, no flavor and liquid appearance negatively penalized the acceptance of yogurts, while presenting a firm consistency and thick texture increased the acceptability. It is concluded that the information contained in the product packaging influences the sensory profile of coconut yogurt. Thus, researchers and food industries must consider possible individual effects, the research scenario and the conditions for evaluating products that may globally interfere in the sensory profile of yogurts.